Maternal health services utilization among mothers in a rural municipality - Ghimire, Nirmala; Agrawal Khatry, Roshani; Shakya, Vivechana (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Maternal health is essential to ensure the good health of the mother as well as children and by extension, the whole family. Despite the various measures launched by the government to enhance maternal care services, the utilization remains at large. Method: A community-based face to face interview was conducted using a pre-tested structured survey questionnaire to find out maternal health service utilization among mothers in Mahankal Rural Municipality, Lalitpur, Nepal, during Feb-Jun 2020. A probability simple random sampling was used to select mothers having children aged between 1 to 3 y. A score of ≥mean was considered good utilization and below it a poor utilization. The study was approved by the ethical committee. The SPSS 16 was used for descriptive (frequency, mean) and comparative analysis by chi square between demographics and health service utilization. Result: There were a total of 178 mothers surveyed, the mean age of 25.9±4.4 y, 77(43.3%) had completed elementary school, and 147(82.6%) were farmers. Good utilization of maternal health service 98(55%) and poor utilization 80(45%). The majority 153(86%) had ≥4 Antenatal checkups, 55(30.9%) had delivered at home despite the government incentive for institutional delivery, 105(59%) had postnatal visits ≥1, and 18(10%) had 3 postnatal visits. Conclusion: The study revealed that slightly more than half (55%) of mothers surveyed had good utilization of maternal health services.